Recent advances in 3D printing sacrificial templates for fabricating engineered vasculature - Li, Shuai; Li, Hangyu; Shang, Xiushuai; He, Jiayan; Hu, Yihe (MedComm - Biomaterials and applications, 2023)
Fabricating engineered vasculature within biological scaffolds is one of the most common strategies to maintain high cell viability before implantation. Many studies have been conducted from the aspects of the manufacturing process, materials science, and cell biology to fabricate engineered vasculature with the aim of enhancing the integration between scaffold and host. Among them, the method of combining three‐dimensional (3D) printing and sacrifice‐based technique has attracted extensive attention. Taking advantage of 3D printing, the method of separating the printed sacrificial template from the biological scaffold to form a 3D channel has become a widely used approach to advance the engineered vasculature. With the development of 3D printing techniques and material science, numerous sacrificial materials have shown their potential in fabricating engineered vasculature. However, several issues remain in this multimethod design, including, but not limited to, the printing process, removal method of sacrificial material, and cell seeding method. This review aims to summarize recent strategies for 3D printing sacrificial templates for fabricating engineered vasculature. The pros and cons of sacrificial materials used in these studies are analyzed. Future perspectives are proposed to fabricate biomimetic‐engineered vasculature. Flexible fabrication processes and materials should be advanced to support the 3D printing of sacrificial templates.